High Premature Morality Rates Among Men in Lithuania. Patttterns and Causes - Stumbrys, Daumantas (Socialinė teorija, empirija, politika ir praktika, 2014)
SummaryThe mortality pattern of the post-soviet population shows a notable life expectancy differentiation by sex, marital status, education, place of residence, and other socio-demographic variables. This publication presents results of a study of mortality patterns among working-age men in Lithuania. The study is based on the Cockerham health lifestyle theory. The main purpose of the study is to evaluate men’s mortality fluctuation since the year 1959. The Lithuanian mortality rates were compared with the mortality rates in other European countries. This study is based on data from the Human Mortality Database and the European Mortality Database. The results of the study confirm that for men the probability to die in the working age in Lithuania is more than twice as high as in France. The Lithuanian working-age men’s population has a very high rate of mortality from external causes and alcohol-related deaths. This research is funded by the European Social Fund under the Global Grant measure (project No. VP1-3.1-ŠMM-07-K-02-067).Key words: causes of death, mortality differentials, men’s premature mortality